2023
DOI: 10.3171/2022.8.spine22755
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, mechanism, and protective strategies for 2-year pelvic fixation failure after adult spinal deformity surgery with a minimum six-level fusion

Abstract: OBJECTIVE The purpose of this study was to determine the incidence, mechanism, and potential protective strategies for pelvic fixation failure (PFF) within 2 years after adult spinal deformity (ASD) surgery. METHODS Data for ASD patients (age ≥ 18 years, minimum of six instrumented levels) with pelvic fixation (S2-alar-iliac [S2AI] and/or iliac screws) with a minimum 2-year follow-up were consecutively collected (2015–2019). Patients with prior pelvic fixation were excluded. PFF was defined as any revision t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…The addition of interbody cages also provides anterior column support, serving as a fulcrum for the production of lordosis; its use with multirod constructs increases the overall rigidity across the PSO site. 16,32 To our knowledge, this report is the first clinical investigation to highlight the SE-PSO technique used in patients with ASD with FSM. The preliminary results support further investigations in the use of the SE-PSO technique in select patients with ASD and are in accordance with previously reported clinical observations and biomechanical investigations.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The addition of interbody cages also provides anterior column support, serving as a fulcrum for the production of lordosis; its use with multirod constructs increases the overall rigidity across the PSO site. 16,32 To our knowledge, this report is the first clinical investigation to highlight the SE-PSO technique used in patients with ASD with FSM. The preliminary results support further investigations in the use of the SE-PSO technique in select patients with ASD and are in accordance with previously reported clinical observations and biomechanical investigations.…”
Section: Discussionmentioning
confidence: 91%
“…Different configurations in multirod constructs with adjacent interbody cages were evaluated, 23 with findings suggesting that an increased number of rods crossing the lumbosacral junction were associated with decreased instrumentation failure. 32 Lee et al retrospectively evaluated factors that were associated with reduced mechanical complications in 253 patients who underwent long-fusion deformity correction with pelvic fixation. They found that accessory rods with the lower instrumented vertebrae to S2/ilium vs S1 and the number of rods crossing the lumbopelvic junction were protective factors against instrumentation failure.…”
Section: Discussionmentioning
confidence: 99%
“…Although SPF indeed reinforces the construct stiffness, 12.0%–46.9% of implant failure rate has been reported by previous studies ( Park et al, 2021b ; Gao et al, 2021 ). To reduce the incidence of mechanical complications, multiple pelvic screws or multirod construct have been applied as an advanced SPF technique ( Uotani et al, 2021 ; Lee et al, 2022a ; Lee et al, 2022b ; Tang et al, 2022 ). The current study revealed that both multiple pelvic screws and multirod construct could increase the mechanical stability of LSJ, reduce strain on the lumbosacral rod, and protect the S1-PS and sacrum.…”
Section: Discussionmentioning
confidence: 99%
“…Although the application of SPF, the incidence of implant failure is still unsatisfactory, with reported rates ranging from 12.0% to 46.9% ( Park et al, 2021b ; Gao et al, 2021 ). In recent cohort studies, advanced SPF technique by multiple pelvic screws or multirod construct has been recommended following long spinal fusion to stabilize the LSJ further, protect the primary rod and screws, and reduce the persistent motion of SIJ ( Uotani et al, 2021 ; Lee et al, 2022a ; Lee et al, 2022b ). However, there was only one small-size cohort study reporting the application of combining the multiple pelvic screws and multirod construct, without any control groups ( Shen et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a total of 10 studies were included in this meta-analysis. 11,13,14,18,19,[24][25][26][27][28] The detailed selection process is illustrated in Fig. 1.…”
Section: Literature Searchmentioning
confidence: 99%